Consequence modelling using ALOHA for estimation of toxic gas dispersion from a chemical plant and evacuation planning in Teluk Kalong Industrial Area - Amiera, Saidi (2016)
The aim of this study is to estimate the toxic gas dispersion by using consequences modelling software which is Areal Location of Hazardous Atmosphere, ALOHA version 5.4.7 at one of chemical plant in Teluk Kalong Industrial Area, Kemaman, Terengganu for the whole year starting from January to December of 2016.The result of this study have been analyzed with a view to determine the threat zone and estimate toxic gas dispersion which is the release of sulfuric acid from the storage tank from the source point for the worst case. Analysis of 12 simulations of toxic gas dispersion for the whole year has also been done to assess the damage potential of such events. It is revealed that toxic gas dispersion poses a great risk as it can disperse up to 1.3 miles not to only workers but also to the public. The study highlights the need for having safe evacuation route at the risky area in chemical plant.